Efficacy and safety of low dose aspirin plus clopidogrel in the treatment of elderly patients with symptomatic intracranial artery stenosis - Song, Hai-xia; Zhang, Bin; Liu, Shan; Shi, Zhi-chao; Wang, Zi-yun; Lu, Hai-li; Yao, Jie; Chen, Juan (Frontiers in Neurology, 2023)
Background: Symptomatic intracranial artery stenosis (sICAS) is a great threat to public health, and its financial burden is substantial, with annual direct high medical costs particularly in China. Currently, the long-term use of conventional dual antiplatelet therapy (DAPT) as the primary modality of treatment for sICAS decreases the risk of stroke recurrence but increases the risk of bleeding. We aimed to evaluate the efficacy and safety of low dose aspirin plus clopidogrel for the treatment of sICAS in the elderly population. Methods: This randomized, controlled study included 181 older patients with transient ischemic attack (TIA) or ischemic stroke (IS) attributed to sICAS, who were recruited between April2015 and November 2020. Efficacy and safety analyses were done in this trial. Results: 181 eligible elderly patients with sICAS were enrolled in this trial. 75 participants were with TIA and 106 with IS. The median time of follow-up was 30 months ranged 1 to 36 months. 90 patients were assigned randomly to the low dose group and 91 patients to the conventional group. The rate of primary, secondary and composite efficacy were not significantly different between the low dose and conventional group (P＞0.05). The rate of composite safety outcome was 7.8% (7/90) in the low dose group, which was lower than 17.6% (16/91) in the conventional group (χ2=3.921, P=0.048). At the time of last follow-up, 17 (9.4%) of 181 patients developed GI injuries, which occurred in 4 (4.4%) of 90 patients in the low dose group and in 13 (14.3%) of 91 patients in the conventional group (χ2 =4.058, P=0.044). The primary efficacy outcome occurred in 6 (18.2%) of 33 patients with severe sICAS and in 22 (38.6%) of 57 patients with moderate sICAS (χ2=4.064, P=0.044) in the low dose group. Conclusion: The safety of low dose aspirin combined with clopidogrel proved to be equally efficient and significantly safer than those of conventional dose within 24 months in elderly patients with sICAS. However, the small size of this study limits the validity of the results. Further trials are necessary to evaluate the role of low dose DAPT in the patients with sICAS.